Smallholder Fishermen’s Welfare: Material, Relational, and Subjective Perspectives - Sutanto, Himawan Arif; Rachmansyah, Yanuar; K Hidayatullah, Surya Kusuma; Enggar M, Arinta; Noviana, Poppy Budi (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Smallholder fishermen make a significant contribution to food security and are an important pillar of economic and social welfare for coastal communities. This study aims to analyze the welfare level of small-scale fishermen in Pemalang Regency based on material, relational, and subjective perspectives. The sample in this study was 95 captured fishermen who were taken using accidental sampling. Data analysis was conducted using descriptive methods and indices calculated based on three perspectives: material, relational, and subjective. The results show that the welfare level of smallholder fishers in Pemalang Regency is generally in the medium category. Fishermen with a low welfare level amounted to 4.2%; fishermen with a medium welfare category amounted to 82.1%; and fishermen with a high welfare category amounted to 13.7%. These findings highlight the importance of holistic and sustainable policy interventions to improve fishermen’s welfare. Several strategies that can be implemented include improving access to capital, skills training, supporting infrastructure development, and strengthening social networks. Through this comprehensive approach, it is expected that the welfare of smallholder fishermen in Pemalang Regency can be significantly improved, so that smallholder fishermen can contribute more to economic and social development in the region.